Leaky gut, circulating immune complexes, arthralgia, and arthritis in IBD: coincidence or inevitability? - Jin, Xi-ya; Li, Dan-dan; Quan, Wei; Chao, Yang; Zhang, Bin (Frontiers in Immunology, 2024)
Most host-microbiota interactions occur within the intestinal barrier, which is essential for separating the intestinal epithelium from toxins, microorganisms, and antigens in the gut lumen. Gut inflammation allows pathogenic bacteria to enter the blood stream, forming immune complexes which may deposit on organs. Despite increased circulating immune complexes (CICs) in patients with inflammatory bowel disease (IBD) and discussions among IBD experts regarding their potential pathogenic role in extra-intestinal manifestations, this phenomenon is overlooked because definitive evidence demonstrating CIC-induced extra-intestinal manifestations in IBD animal models is lacking. However, clinical observations of elevated CICs in newly diagnosed, untreated patients with IBD have reignited research into their potential pathogenic implications. Musculoskeletal symptoms are the most prevalent extra-intestinal IBD manifestations. CICs are pivotal in various arthritis forms, including reactive, rheumatoid, and Lyme arthritis and systemic lupus erythematosus. Research indicates that intestinal barrier restoration during the pre-phase of arthritis could inhibit arthritis development. In the absence of animal models supporting extra-intestinal IBD manifestations, this paper aims to comprehensively explore the relationship between CICs and arthritis onset via a multifaceted analysis to offer a fresh perspective for further investigation and provide novel insights into the interplay between CICs and arthritis development in IBD.